Music and Queered Temporality in Slave Play - Wilson, Imogen (Current Musicology, 2020)
This paper considers the representational role of music in theatre, and how music can help to communicate complex elements of ‘lived time’. I extract case studies from Jeremy O. Harris’ Slave Play (2019), a recent Broadway production which explores the impact in contemporary America of inherited trauma from slavery, by interrogating the sexual power imbalances within three interracial couples. Both characters exhibit musical hallucinations associated with their obsessive-compulsive disorder. I theorize how the musical examples emerge as an indirect emotional and temporal byproduct of the struggles facing two of the characters. I argue that their hallucinations ‘suspend’ lived time, and are an attempt to overcome “restriction, uncertainty, and blockage,” with regard to their intimate relationships (Sara Ahmed 2006, p.139). I consider much of the music in Slave Play to perform a metadiegetic function. The secondary narration, constructed by ‘queer time’, is represented through the two popular musical examples, Rihanna’s “Work” (2016) and Unknown Mortal Orchestra’s “Multi-Love.” Both songs are ridden with intertextual significance, and are integrated meaningfully into the temporality of the play through Harris’ autofictional approach to writing. Slave Play stands at the forefront of a budding genre of theatre, one which largely does away with traditional theatrical convention by blending the distinction between musical and traditional theatre. This requires a novel academic approach—drawing from both musical and traditional theatre scholarship, queer theory, and philosophies of time and music.